Advanced Shape Memory Technology for Biomedical Engineering - Abhijit Vijay Salvekar; Wei Min Huang; Subbu S Venkatraman (Archive of Biomedical Science and Engineering - Peertechz Publications, 2016)
The ability to recover to the original shape only at the presence of the right stimulus is traditionally known as the shape memory effect (SME) [1]. The materials with such a capability are technically termed shape memory materials (SMMs) [2]. Typical SMMs include shape memory alloy (SMA) and shape memory polymer (SMP, including hydrogel), while typical stimuli are temperature (thermo-responsive, both heating or cooling), chemical (chemo-responsive, including water), light (photo-responsive) and magnetic (magneto-responsive)[3]. Although SMMs have been mostly used for actuators in the past,they have been proposed for new types of sensors as well, but not so successful till today [4-7].